The Beginning of Senior Career in Team Sport Is Affected by Relative Age Effect - Lupo, Corrado; Boccia, Gennaro; Ungureanu, Alexandru Nicolae; Frati, Riccardo; Marocco, Roberto; Brustio, Paolo Riccardo (Frontiers in Psychology, 2019)
Many previous studies in national team sports did not report evidence about relative age effect (RAE) in senior categories. This study aimed for the first time to determine if the RAE may specifically affect the early, but not the late, phase of senior career in elite team sports. A total of 3,319 birthdates (basketball: n=642; rugby: n=572; soccer: n=1318; volleyball: n=337; water polo: n=450) of elite senior players were analysed. Senior players with an age lower or equal to the 25° percentile of age were considered as early phase players while the others as late phase players. Separate Poisson regression models were applied to investigate the RAE in each sport (overall, and for early phase and late phase subgroups). Considering the overall sample, players born close to the beginning of the year were 1.57, 1.34, 2.69, 1.48 and 1.45 times more likely to reach 1st and 2nd Italian division of basketball, rugby, soccer, volleyball, and water polo respectively than those born in the last part of the year. RAE was present in all early phase subgroups. Differently, in the late phase subgroups the RAE was present only in soccer. Data highlighted a bias in the selection of senior teams, which may limit the chance to identify talented players born late in the second part of the year. Italian sport federations should promote the talent development of relatively younger players by equally promoting the joining of young players to senior teams.